C++ fundamentals - Mallia, Antonio; Zoffoli, Francesco (Packt Publishing, 2019)
Write high-level abstractions while retaining full control of the hardware, performances, and maintainability. Key Features Transform your ideas into modern C++ code, with both C++11 and C++17 Explore best practices for creating high-performance solutions Understand C++ basics and work with concrete real-world examples Book Description C++ Fundamentals begins by introducing you to the C++ compilation model and syntax. You will then study data types, variable declaration, scope, and control flow statements. With the help of this book, you'll be able to compile fully working C++ code and understand how variables, references, and pointers can be used to manipulate the state of the program. Next, you will explore functions and classes - the features that C++ offers to organize a program - and use them to solve more complex problems. You will also understand common pitfalls and modern best practices, especially the ones that diverge from the C++98 guidelines. As you advance through the chapters, you'll study the advantages of generic programming and write your own templates to make generic algorithms that work with any type. This C++ book will guide you in fully exploiting standard containers and algorithms, understanding how to pick the appropriate one for each problem. By the end of this book, you will not only be able to write efficient code but also be equipped to improve the readability, performance, and maintainability of your programs. What you will learn C++ compilation model Apply best practices for writing functions and classes Write safe, generic, and efficient code with templates Explore the containers that the C++ standard offers Discover the new features introduced with C++11, C++14, and C++17 Get to grips with the core language features of C++ Solve complex problems using object-oriented programming in C++ Who this book is for If you're a developer looking to learn a new powerful language or are familiar with C++ but want to update your knowledge with modern paradigms of C++11, C++14, and C++17, this book is for you. To easily understand the concepts in the book, you must be familiar with the basics of programming. Downloading the example code for this book You can download the example code files for all Packt books you have purchased from your account at http://www.PacktPub.com. If you purchased this book elsewhere, you can visit http://www.PacktPub.com/support and register to have the files e-mailed directly to you.